The Effect of The Implementation of Modernization of The Tax Administration System, Income Level, and Quality of Fiscal Services on Taxpayer Compliance With Taxpayer Awareness as an Intervening Variable - Safitri, Diajeng Nur; Nyimas Wardatul Afiqoh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This study aims to determine the effect of the implementation of modernization of the tax administration system, income level, and quality of fiscal services on taxpayer compliance with taxpayer awareness as an intervening variable. In this study, the researcher examines taxpayer compliance. The population in this study is individual taxpayers who have an NPWP and are registered at KPP Pratama Gresik and these taxpayers have income from the Gresik Regency area. Sampling was conducted using purposive sampling with a total of 95 respondents. This study uses primary data taken in the form of questionnaire answers distributed to taxpayers. This research method is quantitative which uses SmartPLS as a testing tool. The results of the test in this study are the direct influence showing that the implementation of modernization of the tax administration system and income level has a positive and significant effect on taxpayer compliance while the quality of fiscal services and taxpayer awareness have no effect on taxpayer compliance. The implementation of modernization of the tax administration system, income level, and quality of fiscal services have no effect on taxpayer awareness. The results of the indirect hypothesis test show that taxpayers' awareness is not able to mediate the influence of the implementation of modernization of the tax administration system, income level, and quality of fiscal services on the compliance of individual taxpayers.